2013
DOI: 10.1016/j.bbmt.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Advances in the Treatment of Primary Plasma Cell Leukemia: A Focus on Hematopoietic Cell Transplantation

Abstract: Primary plasma cell leukemia (pPCL) is an uncommon but aggressive plasma cell malignancy associated with frequent extramedullary involvement, high-risk cytogenetic abnormalities, and frequent organ dysfunction, ultimately resulting in poor prognosis. Here we review recent advances in our understanding of the molecular and biological aspects of PCL and summarize therapeutic progress occurring over the past 2 decades. pPCL is distinguished from secondary PCL arising from multiple myeloma. The molecular and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 79 publications
0
8
0
2
Order By: Relevance
“…To our knowledge, novel agents and auto-HSCT as consolidation after induction therapy are useful for the treatment of pPCL patients as well as in improving their outcome [13,15,16,17,18,19,20,21]. Recently, Musto et al [22] conducted a first prospective trial of lenalidomide and dexamethasone therapy in a series of previously untreated pPCL patients, and they indicated that the median OS was 28 months after a median follow-up of 34 months.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, novel agents and auto-HSCT as consolidation after induction therapy are useful for the treatment of pPCL patients as well as in improving their outcome [13,15,16,17,18,19,20,21]. Recently, Musto et al [22] conducted a first prospective trial of lenalidomide and dexamethasone therapy in a series of previously untreated pPCL patients, and they indicated that the median OS was 28 months after a median follow-up of 34 months.…”
Section: Discussionmentioning
confidence: 99%
“…2 Poor outcomes seen in some of these patients may have resulted from unfavorable patient-or disease-related characteristics, or both, and it would seem appropriate to offer this intensive therapy only to selected patients, such as those of younger age with adequate performance status and organ function, lack of significant comorbidities, minimal or no disease at the time of alloHCT, and a wellmatched donor. It should be noted that the optimal conditioning and post-alloHCT maintenance regimens as well as GVHD prophylaxis for these patients is unknown, and poor historical outcomes may also have resulted from specific therapy-related toxicities.…”
Section: Discussionmentioning
confidence: 98%
“…1 However, more effective disease control has been achieved with the use of novel agentecontaining regimens, 2 and an overall response rate of nearly 80% has been reported in patients with pPCL receiving bortezomib-based therapies. 3 Similar to patients with multiple myeloma (MM), those with pPCL are frequently offered consolidation with high-dose melphalan followed by autologous stem cell transplantation (ASCT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the 2 largest retrospective series of PPCL patients treated with ASCT have also been recently reviewed [9]. Overall, ASCT was able to induce a higher rate of complete response, but appeared to be less effective than in MM in the long term, due to the short duration of posttransplant response and increased non-relapse-related mortality.…”
mentioning
confidence: 99%